RELATIONSHIP BETWEEN PSYCHOLOGICAL BACK-GROUND AND FLUCTUATION IN HEARING ABILITY IN HEARING-IMPAIRED PATIENTS EXPERIENCING ACUTE LOW-TONE HEARING LOSS - Ishii, Masanori; Umezawa, Yuji; Nakamura, Masahiro; Chikazawa, Satoshi; Moriyama, Hiroshi (JIBI INKOKA TEMBO, 2003)
The STAI, SDS, a health questionnaire, and a stress-check questionnaire were used to evaluate the psychological status of 47 patients with low-tone hearing deficit caused by Meniere's disease, acute low-tone sensorineural hearing loss, or suspected Meniere's disease. Many patients had been under stress prior to occurrence of the low-tone hearing deficit and showed significantly higher tendencies toward anxiety, depression, and autonomic nervous system symptoms compared to the control group. At initial examination, 27 showed high STAI but this decreased 1 month later. In addition, in 20 of these 22 patients, both STAI and hearing had improved after 1 month, but in the 5 patients with no change in hearing STAI remained high even after 1 month. Based on these results, we concluded that stress is a background factor in the causation of acute low-tone sensorineural hearing loss and should be considered as an important factor in attempting to ameliorate this condition.